New vehicle bumper design for pedestrian protection during impact - Samaka H.; Manap A.; Tarlochan F. (Institute of Physics Publishing, 2023)
Crashworthiness; Pedestrian safety; Legform impactor; Lower leg; Lower leg injuries; LS-DYNA; Pedestrian protection; Vehicle bumper; Vehicle safety; Finite element method